Synchronization of motor unit activity during voluntary contraction in man. - Datta, A K (1990)
1. Motor unit synchronization has been studied in human first dorsal interosseous muscle. 2. Two needle electrodes were inserted into the muscle and the activity of pairs of motor units recorded. 3. Pre- and post-stimulus histograms of the firing of unit pairs showed a narrow central peak of duration 1.3-9.3 ms (88% of sample in the range 1-6 ms; mode 3.0 ms), together with a variable amount of synchronization of somewhat longer duration. 4. For the duration of the whole synchronization peak (85% sample in range 5-15 ms; mode between 6.1 and 8.0 ms (31% of sample], units fired between 8 and 485% times more often than would have been expected had the units been firing independently of one another. Amplitudes of the peak of the recorded histograms expressed as a proportion of control ranged from 1.8 to 10.9 (mean 3.9; bin width 160 microseconds). 5. The strength of synchronization between the firing of motor unit pairs was inversely related to differences in recruitment threshold. The largest amount of synchronization was observed for pairs of units in which both had recruitment thresholds less than 0.5 N or greater than 1.0 N. Less synchronization was found between pairs of units in which one had a recruitment threshold less than 0.05 N and the other a threshold greater than 1.0 N. 6. The time course of synchronization was well matched by the predictions of a theoretical model based on the hypothesis that underlying the observed synchronization is the joint arrival of EPSPs from branched last-order input fibres.